Investigating pharmaceutical formulations using advanced analytical techniques - Abouselo, Amjad (2019)
Drug research and development is a costly and lengthy process and involves a high risk of product failure. The consequences of insufficient understanding and poor control of pharmaceutical physicochemical properties and stability during drug development can delay new drug approvals and increase the cost of developing new drugs. Salts, which are estimated to account for >50% of active pharmaceutical ingredient formulations, are susceptible to drug degradation, which can lead to a phase transformation of the drug from a more soluble salt form to the less soluble free form, also known as salt disproportionation. Salt disproportionation has severe implications on final product stability and performance, such as slow dissolution and reduced bioavailability. As a result, determination of salt disproportionation reactions in the later stages of drug development can significantly increase the cost of development due to changes in the final product formulation. Although salt forms are widely utilised in the pharmaceutical industry, salt disproportionation in the presence of relative humidity and excipients is yet to be fully understood. Therefore, the research detailed in this thesis aims to apply simple, fast and in-situ analytical techniques to investigate the effects of relative humidity and formulation excipients on salt disproportionation in multi-component solid dosage forms during storage and dissolution. The application of advanced analytical technologies will provide a fundamental understanding of salt disproportionation in the presence of formulation excipients and thus assist formulators in predicting the instability of the drug salt and identifying formulation strategies to mitigate salt disproportionation at early stages of drug development. The experimental work in this thesis is split into three sections: 1) exploring the capabilities and limitations of advanced analytical techniques in a model complex system; 2) investigating salt disproportionation in the presence of excipients during storage at high relative humidity using in-situ optical screening techniques and 3) the application of in-situ Raman spectroscopy to study salt disproportionation in multicomponent tablets during dissolution. A wide range of state-of-the-art advanced analytical techniques was explored using nanoparticles in electrospun fibre hybrids as a challenging, complex multi-component system (Chapter 3). The particle-fibre hybrid morphology was found to be influenced by the encapsulated particle size and nanoparticle concentration. Transmission electron microscopy (TEM) was found to be more efficient than scanning electron microscopy (SEM) in investigating the particle-fibre hybrid morphology due to the transmission capability. Energy dispersive X-ray (EDX) analysis, Raman spectroscopy and time-of-flight secondary ion mass spectroscopy (ToF-SIMS) were utilised to provide valuable elemental, chemical and surface information of the particle-fibre hybrids, respectively. The salt stability of two salt model systems, Pioglitazone HCl and Ibuprofen sodium, was investigated as a function of different formulation excipients during storage and dissolution in Chapters 4 and 5, respectively. In-situ optical microscopy equipped with a controlled humidity chamber was used to monitor salt disproportionation in drug-excipient binary mixtures (Chapter 4). This was achieved by tracking the changes in the salt crystal morphology due to phase transformation in real-time. Salt disproportionation to the free-form led to a change in the crystal shape from block-like crystals into needle-like crystal structures in both salt model systems. The effect of acidic and alkaline excipients on the microenvironment pH has a significant role in facilitating or preventing salt disproportionation during storage. Salt disproportionation does not only occur in solid-state as described previously but can also take place in the solution. A bespoke set-up combining Raman confocal microscopy and an ultraviolet-visible (UV-Vis) spectroscopy flow cell was used to understand the effect of excipients on salt stability in tablets during dissolution (Chapter 5). Raman spectroscopy was employed to detect chemical changes associated with the formation of the undesirable free form of the drug in the solid tablet matrix. In-line UV-vis spectroscopy was used to monitor the concentration of the drug in solution during dissolution. The results showed the vital role of pH both in the dissolution media and the microenvironment (controlled by the formulation excipients) in inducing or preventing salt disproportionation. Raman mapping and cross-sectioning, using a microtome, were performed after dissolution for tablets that exhibited salt conversion. The Raman maps of the cross-sectioned tablets revealed the formation of a shell consisting of the free drug around the edge of the tablet. This shell decreased the rate of penetration of the dissolution medium into the tablet, which had significant implications on the release of the API into the surrounding solution as shown by the UV-Vis drug release data. Overall, the research in this thesis has demonstrated that the properties of the salt (specifically pHmax), excipient properties (such as pKa, solubility, hydrophobicity), as well as the dissolution medium pH, played essential roles in influencing the disproportionation during storage and dissolution. Analytical techniques such as optical screening and Raman spectroscopy, which can be employed in-line and online, were demonstrated to be effective approaches to investigate salt disproportionation. Results were obtained in real-time and did not require large amounts of solid or extensive sample preparation indicating that these analytical techniques can address the challenges of studying a range of pharmaceutical drug delivery systems, which can ultimately lead to the development of more efficient pharmaceutical formulations.